Nanoparticles Formation of Philippine Carrageenan with pDNA/polyethylenimine and pDNA/Chitosan as Monitored by Atomic Force Microscopy (AFM) for Potential use in Gene Delivery - Briones, Annabelle V.; Sato, Toshinori (Asian Journal of Biological and Life Sciences, 2016)
Philippine carrageenan, was interacted with pDNA/PEI and pDNA/chitosan nanoparticles to study its effect on DNA condensation for potential use in non-viral gene delivery. Complexation and DNA condensation was monitored by atomic force microscopy. A cloud like structure was observed in the image of carrageenan-PEI complex as compared with the complex of carrageenan-chitosan which is more compact showing a fibrous structure. When pDNA was complexed with -carrageenan a distinct morphology was observed. The structure showed the formation of linear strands of DNA into a web-like structure or a network without interlacing with the single stranded chains of carrageenan. Using an N/P ratio of 5, pDNA was not condensed using the different types of carrageenan. All of the images formed a cloud-like or dendritic structures. The complex of chitosan and carrageenan showed a poor medium for DNA condensation as observed in the micrograph. pDNA is more condensed with PEI-carrageenan complex than chitosan-carrageenan combination. The electrostatic interaction of carrageenan with PEI was able to condense the DNA at N/P ratio of 3.3 better than chitosan-carrageenan interaction with an N/P ratio of 5. Comparing the three types of Philippine carrageenan in the interaction of pDNA/PEI, iota type forms a good complex with PEI that can condense DNA, which is an important aspect in gene delivery.
Keywords: Atomic force microscopy; Carrageenan; Chitosan; DNA condensation; Polyethylenimine